2019
DOI: 10.3390/molecules24213898
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Characterization of Physicochemical and Antioxidants Properties of Processed Heterotrigona itama Honey from Different Origins and Classification by Chemometrics Analysis

Abstract: Stingless bee honey produced by Heterotrigona itama from different botanical origins was characterised and discriminated. Three types of stingless bee honey collected from acacia, gelam, and starfruit nectars were analyzed and compared with Apis mellifera honey. The results showed that stingless bee honey samples from the three different botanical origins were significantly different in terms of their moisture content, pH, free acidity, total soluble solids, colour characteristics, sugar content, amino acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 62 publications
3
36
1
4
Order By: Relevance
“…Despite below the limit of detection in the honeys evaluated in the present study, maleic, malonic, tartaric, glutaric, propionic, and aspartic acids were reported in other honeys, such as sunflower, multifloral, chestnut, eucalyptus, citrus, heather, lavender, and thyme (BRUGNEROTTO et al, 2019;HAROUN et al, 2012;KIVRAK, 2015;NOZAL et al, 2003;OHMENHAEUSER et al, 2013). Therefore, AOA and amino acids can contribute in the discrimination of honeys, with high potential in the differentiation of floral and honeydew honeys (AZEVEDO et al, 2017b;HAROUN et al, 2012;SHAMSUDIN et al, 2019), but more studies still need to be conducted to ensure reliable data regarding the botanical and geographical discrimination of honeys.…”
Section: Methods Applicationmentioning
confidence: 48%
“…Despite below the limit of detection in the honeys evaluated in the present study, maleic, malonic, tartaric, glutaric, propionic, and aspartic acids were reported in other honeys, such as sunflower, multifloral, chestnut, eucalyptus, citrus, heather, lavender, and thyme (BRUGNEROTTO et al, 2019;HAROUN et al, 2012;KIVRAK, 2015;NOZAL et al, 2003;OHMENHAEUSER et al, 2013). Therefore, AOA and amino acids can contribute in the discrimination of honeys, with high potential in the differentiation of floral and honeydew honeys (AZEVEDO et al, 2017b;HAROUN et al, 2012;SHAMSUDIN et al, 2019), but more studies still need to be conducted to ensure reliable data regarding the botanical and geographical discrimination of honeys.…”
Section: Methods Applicationmentioning
confidence: 48%
“…Clearly, these observations could be attributed to the different types and concentrations of antioxidant compounds present in the honey samples. Among the different honey marinades used, gelam honey showed the highest (95.14%) inhibitory effect on HCAs, possibly because of the high antioxidant activity (IC 50 ) observed in gelam honey as compared to other honey types as reported in our previous study [ 58 ]. Nevertheless, the results in this study were consistent with the findings by Puangsombat and Smith [ 59 ] and Jamali et at.…”
Section: Resultsmentioning
confidence: 90%
“…This was due to the high internal temperature, cooking loss, and IC 50 values in grilled beef samples marinated with Apis honey than those marinated with stingless bee honey. Honey with high IC 50 value had low antioxidant activity [ 58 ]. This observation clearly showed that Apis honey with the high IC 50 value produced higher HCAs concentration in grilled beef as compared to stingless bee honey, which has lower IC 50 value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations